Predation on Scinax littoralis (Anura: Hylidae) by another treefrog, Hypsiboas albomarginatus (Anura: Hylidae) - Centeno, Fernanda C.; Cicchi, Paulo J.P. [UNESP]; Couto, Fernando M. (My University, 2010)
Herein we report predation by the hylid anuran Hypsiboas albomarginatus on another hylid anuran Scinax littoralis, observed in a remnant of Atlantic Forest in the municipality of Santos, southeastern Brazil.
Keywords: Amphibia; Anura; Atlantic forest; White-edged treefrog; Hyla albomarginata; Hylidae; Scinax